Comparison of Effects of Nalbuphine and Tramadol on Cardiovascular Response to Tracheal Intubation in Patients Undergoing Emergency Appendectomy - Farrukh Ayub, Rub Nawaz Khan, Nauman Anwar Rana, Syed Fazal E Karim Faisal, Rehan Haider, Irtiza Ahmed Bhutta (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To compare the effects of Nalbuphine with Tramadol on cardiovascular response (change in heart rate and blood pressure) to tracheal intubation in patients undergoing emergency appendectomy. Material and methods: This randomized controlled trial was conducted at the Department of Anaesthesiology, CMH Mardan from January 1, 2022, to June 30, 2022. A total of 100 patients who were undergoing emergency appendectomy under general anaesthesia, with ASA grade I, aged between 30-50 years, and weighing between 50-80 kg were selected. Patients were either male or female and had normal blood pressure. They were divided into two groups: the Nalbuphine group and the Tramadol group. The study focused on analyzing the cardiovascular response (changes in heart rate and blood pressure) to tracheal intubation in both groups. Results: Most of the patients in both Group A and Group B were females, with a female to male ratio of 3.54:1 and 2.57:1, respectively. The mean age of patients in Group A was 37.90±5.41, while in Group B it was 40.10±6.39. After laryngoscopy and tracheal intubation, patients in Group A had a significantly less increase in heart rate and blood pressure as compared to those in Group B. Conclusion: The Nalbuphine is better than Tramadol in attenuating the cardiovascular response to laryngoscopy and tracheal intubation. Keywords: Nalbuphine, Tramadol, Cardiovascular Response, Tracheal Intubation, Laryngoscopy, Heart Rate and Blood Pressure.